Translation Memories from Public Agencies - Dahlberg, Simon; Language Council of Sweden, Institute for Language and Folklore (Institute for Language and Folklore, 2020)
Translation memories from different public agencies.

Översättningsminnen från olika myndigheter.
Översättningsminnen från myndigheter
Keywords: public administration; offentlig förvaltning; SOCIETY AND CULTURE; SAMHÄLLE OCH KULTUR; Social Sciences; Samhällsvetenskap; Languages and Literature; Språk och litteratur; Public Administration Studies; Studier av offentlig förvaltning